(untitled) (Mugda Medical College Journal, 2024)
Background: The knowledge of the local pattern of infection and antibacterial sensitivity in Ludwig’s angina is essential to enable efficacious treatment for it. Objective: To find out the pattern of bacteria responsible for developing Ludwig’s angina and their antibacterial susceptibility. Methods: It is a prospective, observational type of study carried out in the Department of Otolaryngology & Head-Neck Surgery, Dhaka Medical College Hospital, Dhaka, and the Department of Clinical Microbiology, ICDDR, B, Dhaka, Bangladesh, between April and September of 2016. A total of 100 patients were included in this study. Results: This study was done among 100 patients. In this study, 42 cases (42%) were in the 31-45 years age group. The male patients were 60 (60%) and females were 40 (40%). Majority of patients 70(70%) came from poor class family with educational level up to HSC (75%), maximum 35(35%) patients use meswak to clean teeth, 70 (70%) patients came from rural area, 70 (70%) patients had dental infection, 25 (25%) patients had diabetes mellitus, all the cases (100%) presented with swelling in the floor of the mouth and neck, pain and tenderness and fever. The major complication was necrotizing fasciitis 8 (8%), 36 (36%) patients were discharged within 1-2 weeks after treatment, Streptococcus 40 (40%) was the most common organism and the most effective antibiotic was Ceftriaxone (65%). Conclusion: The most frequently isolated organism in Ludwig’s angina is Streptococcus and sensitivity results showed a majority of isolates are susceptible to Ceftriaxone. Mugda Med Coll J. 2023; 6(2): 71-76